Integrating point-of-care diabetes detection with lifestyle counselling in community settings: outcomes from Western Sydney, Australia - Jaybee Serrano; Gideon Meyerowitz-Katz; Janine Dawson; Aruni Ratnayake; Sumathy Ravi; Helen Dick; Sian Bramwell; Mark Scott; Rajini Jayaballa; Glen Maberly (BMC, 2024)
Abstract Introduction Early detection and prevention of type 2 diabetes and its complications are global health priorities. Optimal outcomes depend on individual awareness and proactive self-management of health risks. This study evaluates the effectiveness of a community-based diabetes detection and intervention program in a high-risk area in western Sydney, Australia. Research design and methods We collaborated with the Workers Lifestyle Group, Tamil Association Arts and Culture Association, and the National Aboriginal and Islanders Day Observance Committee to implement our program. Participants underwent HbA1C testing via point-of-care blood spot testing. They received personalized feedback, education on diabetes management, and were offered opportunities to enrol in lifestyle modification programs. Participants identified with pre-diabetes (HbA1C 5.7-6.4%) or diabetes (HbA1C > 6.4%) were advised to consult their General Practitioners (GPs). A follow-up questionnaire was distributed 3-8 months post-intervention to evaluate the programs usefulness and relevance and lifestyle changes implemented by the participants. Results Over eight months, 510 individuals participated. Of these, 19% had an HbA1C > 6.4%, and 38% had levels between 5.7 and 6.4%. Among those with diabetes, HbA1C levels ranged as follows: 56% <7%; 20% 7-7.9%; 18% 8-8.9%; and 5% >9%. Post intervention survey indicated that the program was well-received, with 62.5% of responses reporting lifestyle changes and 36.3% seeking further advice from their local healthcare providers. Conclusion The study demonstrates a significant prevalence of pre-diabetes and diabetes in the community, similar to findings from larger-scale hospital and general practice studies. Point-of-care testing combined with personalized education effectively motivated participants toward healthier lifestyle choices and medical consultations. The paper discusses the scalability of this approach for broader population.